Розвиток інтеграційних процесів: проблеми та перспективи українських товаровиробників - Романчик, Тетяна Володимирівна (Українська державна академія залізничного транспорту, 2014)
Участь України у міжнародних інтеграційних процесах є умовою формування економічної стабільності країни, затвердження її позицій в системі міжнародних відносин. Вихід вітчизняних товаровиробників на європейський ринок – питання, яке в останні часи набуло особливої актуальності. В статті розглядаються перспективи, що відкриваються перед вітчизняними підприємствами з їх виходом на європейський ринок та проблеми, які потребують негайного подолання.

Ukraine's participation in international integration processes is the condition for the formation of economic stability, the approval of its position in international relations. This paper analyzes the perspectives opening to Ukrainian producers in the European market, but also highlights the problems that accompany the process and require immediate solution. With the release of domestic producers in developed European market, they receive a number of additional opportunities for both individual businesses and for the country as a whole. But should be noted that when domestic producers entering foreign markets are starting to compete at a higher level. Their products must comply with market counterparts in terms of quality and price parameters. Unreadiness of companies to this step caused by the high level of depreciation, outdated manufacturing technologies, the difference between parameters of quality for the products in Ukraine and the European Union.
Development of integration: issues and perspectives of Ukrainian commodity
Keywords: інтеграція; європейський ринок; вітчизняні товари; інтеграційні процеси; integration; European Union integration process; European market; domestic goods